Naphthalene degradation by Pseudomonas sp. strain LBKURCC149 with the addition of glucose as co-substrate (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Novianty R, Antika B, Saryono, Awaluddin A, Pratiwi NW, Juliantari E. 2022. Naphthalene degradation by Pseudomonas sp. strain LBKURCC149 with the addition of glucose as co-substrate. Biodiversitas 23: 5654-5661. Naphthalene is one of the pollutants that cause carcinogens. The biodegradation of carcinogenic naphthalene toxic compounds needs to be done to control pollution. Pseudomonas is one of several bacterial species that can degrading naphthalene. This study aimed to test the effectiveness of Pseudomonas sp. isolated from the land area of ??the Joint Operating Body (JOB) of PT. Siak Bumi Pusako-Pertamina Hulu in degrading naphthalene with glucose as a co-substrate. The potency of three isolates of Pseudomonas sp. LBKURCC148, LBKURCC149, and LBKURCC150 was tested in Minimal Media (MM) containing 0.2 mM naphthalene and incubated for seven days. The Optical Density (OD), pH, decreased concentration of naphthalene and degradation ability parameters were analyzed using UV-Vis spectrophotometer. The results showed that Pseudomonas sp. LBKURCC149 was able to degrade naphthalene by 13.95%. Naphthalene analysis using HPLC resulted in a decrease in the peak area of ??the sample as compared to the control. Based on these findings Pseudomonas sp. LBKURCC149 could be recommended to use to degrade naphthalene pollution.
Keywords: Biodegradation, glucose, naphthalene, Pseudomonas